Report Rapid Transit Corridors Delhi - Planning Commission (Planning Commission, 1974)
Delhi’s rapid population growth and urbanization since 1947 have led to severe traffic congestion and rising road accidents, exposing the inadequacy of the existing bus-based public transportation system. Comprehensive traffic studies highlighted the urgent need for a Mass Rapid Transit System (MRTS) to provide a multi-modal, integrated solution connecting densely populated areas with key economic zones. Proposed North-South and East-West corridors, supported by feeder lines, are designed to accommodate projected daily trips of up to 20 million by 1981. Effective implementation requires government investment, administrative coordination through a Metropolitan Transport Authority, and immediate upgrades to existing public transport infrastructure, ensuring sustainable urban mobility and reduced reliance on private vehicles.
Government of India Metropolitan Transport Team Planning Commission New Delhi, June, 1974.
Government of India Metropolitan Transport Team Planning Commission
Keywords: Delhi Urban Transport; Mass Rapid Transit System; Traffic Congestion; Public Transportation; Urban Mobility; North-South Corridor; East-West Corridor; Feeder Lines; Vehicle Growth; Road Safety; Metropolitan Transport Authority; Multi-Modal Transport